The ministerial priesthood and liturgical anamnesis in the thought of Edward J. Kilmartin, S.J. - Hahnenberg, Edward P. (Theological studies, 2005)
The article explores the possibilities for a constructive theology of priesthood drawn from the work of Edward J. Kilmartin, S.J. (1923-1994). Placing Kilmartin's direct treatment of church office within the context of his larger theological project, the author names the unstated thesis guiding Kilmartin's approach: the ministerial priesthood serves the memory of Christ. The article concludes that Kilmartin's understanding invites reflection on the ministerial priesthood in light of Jesus' life, pneumatology, faith, and the category of priesthood itself.